Potensi Ekstrak Teh Hijau (Camellia sinensis) Terhadap Peningkatan Jumlah Sel Fibroblas Soket Pasca Pencabutan Gigi pada Tikus Wistar (The Potency of Green Tea Extract [Camellia sinensis] Against Increase of Fibroblast Cells on Socket Post Tooth Extracti - Pandika Agung Kurnia; Hengky Bowo Ardhiyanto; Suhartini . (Pustaka Kesehatan, 2015)
In dentistry, tooth extraction is a frequent maintenance treatment. Thing to consider is healing process after extraction. Healing process consists of three phases, I.e. inflammation, fibroblastic and remodeling. Plants that are believed to accelerate wound healing is green tea. This study was aimed to look at the number of fibroblast cells after tooth extraction that was given by green tea extract (Camellia sinensis). This research was an experimental laboratory with the post-test only control group design. The samples were 24 male Wistar rats and divided into 2 groups: control group and treatment group. Each group was further divided into 3 subgroups, 3rd day, 5th day, 7th day . After extraction of left mandibular first molar tooth, rats in treatment group were given by green tea extract every day until they were decapitated according to appointed day. Tissue was histologically processed by HE staining. Count of fibroblast cells was done under a microscope on 3 field of views  with magnification 400x. Data were analyzed by using Independent T-test and it showed that on 3rd p=0,777, on 5th p=0,000, and on 7th p=0,048. Based on analysis, it could be concluded that the number of fibroblast cells in treatment group were more that in control group.   Keywords: fibroblasts, green tea extract, tooth extraction, wound healing.